2019
DOI: 10.26905/enjourme.v4i2.3708
|View full text |Cite
|
Sign up to set email alerts
|

Genre preferences in Reading Comprehension materials in first level English book of Senior High School

Abstract: This study aimed to know genre preferences in the reading comprehension material in first level English book of senior high school. This study, which is employed a qualitative-narrative technique with no statistical analysis, described some material for reading comprehension material, such as descriptive text, narrative text, and recount text. This study revealed that the reading comprehension materials in first level English book of senior high school was presented into ten reading comprehension materials. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Moreover, the result of this study was similar to the result of Panjaitan et al (2019) study entitled "Genre preferences in Reading Comprehension materials in first level English book of Senior High School". The result of the previous study revealed that genre preferences in the reading comprehension materials in first level English book senior high school was presented into three genre preferences: descriptive text, recount text, and narrative text.…”
Section: The Types Of Text For Supplementary Reading Materials Chosen By Students Based On Their Preferences At Grade VIII Of Smpn 1 Kepasupporting
confidence: 84%
“…Moreover, the result of this study was similar to the result of Panjaitan et al (2019) study entitled "Genre preferences in Reading Comprehension materials in first level English book of Senior High School". The result of the previous study revealed that genre preferences in the reading comprehension materials in first level English book senior high school was presented into three genre preferences: descriptive text, recount text, and narrative text.…”
Section: The Types Of Text For Supplementary Reading Materials Chosen By Students Based On Their Preferences At Grade VIII Of Smpn 1 Kepasupporting
confidence: 84%